Especificação do tamanho da defasagem de um modelo dinâmico - Furlan, Camila Pedrozo Rodrigues (Universidade Federal de São Carlos, 2009)
Several techniques are proposed to determine the lag length of a dynamic regression model. However, none of them is completely satisfactory and a wrong choice could imply serious problems in the estimation of the parameters. This dissertation presents a review of the main criteria for models selection used in the classical methodology and presents a way for determining the lag length from the perspective Bayesian. A Monte Carlo simulation study is conducted to compare the performance of the significance tests, R2 adjusted, final prediction error, Akaike information criterion, Schwarz information criterion, Hannan-Quinn criterion, corrected Akaike information criterion and fractional Bayesian approach. Two estimation methods are also compared, the ordinary least squares and the Almon approach.
Keywords: Análise de séries temporais; Modelos econométricos; Seleção de modelos; Mínimos quadrados; Método de Almon; Dinamic models; Lag length selection; Ordinary least squares method; Almon method; Monte Carlo simulation; CIENCIAS EXATAS E DA TERRA::PROBABILIDADE E ESTATISTICA::ESTATISTICA